NiMo-based crystalline / amorphous heterostructure composite material as well as preparation method and application thereof

By using NiMo-based crystalline/amorphous heterostructure composite materials as electrocatalysts, the problems of slow kinetics of water electrolysis hydrogen production reaction and high cost of platinum-based materials are solved, and efficient, low-cost and stable alkaline water electrolysis hydrogen production reaction is achieved.

CN119753734AActive Publication Date: 2025-04-04JIANGXI NORMAL UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411807880.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-04
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

In the prior art, the kinetic process of water electrolysis hydrogen production reaction is slow, and the insufficient durability, scarce resources and high costs of platinum-based materials limit their large-scale commercial applications.

Method used

The NiMo-based crystalline/amorphous heterostructure composite material is used as an electrocatalyst to prepare the material through electrochemical peeling, chemical synthesis and high-temperature annealing. Crystal Ni is used to promote efficient electron transfer of amorphous NiMoB structure, increasing and enhancing active sites.

Benefits of technology

The kinetics of alkaline water electrolysis hydrogen production reaction are significantly improved, and excellent electrocatalytic characteristics are shown, including low overpotential, fast kinetics and high stability, reducing hydrogen production costs and improving system stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753734A_ABST
    Figure CN119753734A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electro-catalytic hydrogen evolution, and particularly relates to a NiMo-based crystalline / amorphous heterostructure composite material and a preparation method and application thereof. The method comprises the following steps: immersing a pair of nickel wires in a NaOH solution, carrying out electrochemical stripping, centrifugal washing and ultrasonic treatment under the voltage of alternating current to obtain a Ni element-containing nanosheet dispersion liquid, dropwise adding the Ni element-containing nanosheet dispersion liquid into an ethanol solution containing MoCl5, stirring, dropwise adding a sodium borohydride solution, and carrying out stirring reaction, centrifugation, washing and drying to obtain precursor powder of the composite material; and finally, putting into a tubular furnace, keeping a flowing hydrogen / argon mixed atmosphere, and carrying out high-temperature annealing treatment. The invention provides an electronic modulation strategy of a NiMo-based crystalline / amorphous heterostructure, so that crystalline Ni promotes efficient electron transfer of an amorphous NiMoB structure, thereby improving the number of active sites and enhancing the site activity; the HER process potential barrier can be reduced, HER dynamics can be accelerated, and excellent HER performance is shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of electrocatalytic hydrogen evolution, and specifically relates to a NiMo-based crystalline / amorphous heterostructure composite material and a preparation method and application thereof. Background Art

[0002] As an environmentally friendly strategy, water electrolysis can produce zero-carbon hydrogen fuel on a large scale using electricity generated by renewable energy such as solar energy and wind energy. It is of great strategic significance for solving the energy crisis and promoting carbon neutrality. However, the high dissociation energy of water molecules leads to high overpotential, which makes the kinetic process of hydrogen evolution reaction (HER) slow. Although platinum-based materials are considered to be ideal electrocatalysts due to their excellent HER performance, their insufficient durability, scarce resources and high cost limit their large-scale commercial application. Therefore, the development of efficient, low-cost and stable electrocatalysts to improve alkaline HER kinetics is crucial to promote the commercialization of water electrolysis hydrogen production technology. These catalysts will help reduce the cost of hydrogen production, improve system stability, and ultimately achieve large-scale, economical and sustainable production of hydrogen energy. Summary of the invention

[0003] The purpose of the present invention is to solve the deficiencies of the prior art and provide a NiMo-based crystalline / amorphous heterostructure composite material and a preparation method and application thereof, specifically adopting the following technical solutions: In a first aspect, the present invention provides a method for preparing a NiMo-based crystalline / amorphous heterostructure composite material, comprising the following steps: S1: immersing a pair of nickel wires in a NaOH solution, electrochemically exfoliating under an alternating current voltage, centrifugally washing, and ultrasonicating to obtain a dispersion of Ni-containing nanosheets; S2: adding the dispersed liquid of the Ni element nanosheets to the ethanol solution containing MoCl5, stirring, then adding the sodium borohydride solution, stirring for reaction, centrifuging, washing, and drying to obtain a precursor powder of the composite material; S3: placing the precursor powder of the composite material in a tubular furnace and maintaining a flowing hydrogen / argon mixed atmosphere for high temperature annealing to obtain the NiMo-based crystalline / amorphous heterostructure composite material.

[0004] The present invention can utilize crystalline transition metals to promote efficient electron transfer in amorphous alloy structures by adopting an electronic modulation strategy of a crystalline (Ni) / amorphous (NiMoB) alloy heterostructure. Among them, the introduction of boron elements can induce the formation of lattice defects and amorphous structures, thereby regulating the electronic structure of the main material and generating electrocatalytic unsaturated coordination active sites, which not only increases the number of active sites but also enhances the activity of the sites. It can perfectly improve the problem that a large number of defects in amorphous electrocatalysts in the prior art increase the complexity of electron transfer and lead to high charge transfer resistance. In addition, the Ni-based alloy in the present invention shows excellent effects in the alkaline HER process due to its ideal hydrogen adsorption activity, and exhibits more superior electrocatalytic properties due to its abundant surface dangling bonds and unsaturated coordination sites.

[0005] As a further preferred embodiment, the NiMo-based crystalline / amorphous heterostructure composite material is a heterostructure formed by crystalline Ni and amorphous NiMoB; the lattice distance in the NiMo-based crystalline / amorphous heterostructure composite material corresponds to Ni (111).

[0006] As a further preferred embodiment, the Ni content in the NiMo-based crystalline / amorphous heterostructure composite material is 10 wt%-20 wt%, and the Mo content is 50 wt%-70 wt%.

[0007] As a further preferred embodiment, the volume ratio of the dispersion of the Ni-containing nanosheets, the ethanol solution containing MoCl5 and the sodium borohydride solution is 10:5:2. In the preparation process of the present invention, a too low Ni / Mo ratio is not conducive to the precipitation of crystalline Ni; a too high Ni / Mo ratio causes Mo and Ni to form an alloy crystalline precipitation. Therefore, too high or too high Ni / Mo ratios are not conducive to the formation of NiMo-based crystalline / amorphous heterostructure composite materials with high performance hydrogen evolution activity.

[0008] As a further preferred embodiment, the mass concentration of the Ni-containing nanosheet dispersion is 1 mg·mL -1 ~ 3 mg mL -1 ; The mass concentration of the ethanol solution containing MoCl5 is 20 mg·mL -1 ~25 mg mL -1 ; The mass concentration of sodium borohydride solution is 30 mg·mL -1 ~ 50 mg mL -1 .

[0009] As a further preferred embodiment, the voltage of the alternating current is 7 V to 9 V; and the time of the electrochemical stripping is 80 min to 120 min.

[0010] As a further preferred embodiment, the specific parameters for maintaining the flowing hydrogen / argon mixed atmosphere are: -1 ~ 70 mL·min -1 A 10% hydrogen / 90% argon mixed atmosphere was introduced at a gas flow rate of .

[0011] As a further preferred embodiment, the specific parameters of the high temperature annealing treatment are as follows: At 5 ℃·min -1 The heating rate was increased from room temperature to 400 ℃~600 ℃, then maintained for 0.5 h~2 h, and finally cooled naturally to room temperature.

[0012] In a second aspect, the present invention provides a NiMo-based crystalline / amorphous heterostructure composite material prepared by the above preparation method.

[0013] In a third aspect, the present invention provides the use of the above-mentioned NiMo-based crystalline / amorphous heterostructure composite material as an electrocatalyst in the electrolytic decomposition of water for hydrogen evolution reaction.

[0014] The beneficial effects of the present invention are: (1) The preparation method of the present invention is simple to operate and has strong repeatability. It proposes an electron modulation strategy for NiMo-based crystalline / amorphous heterostructures, so that crystalline Ni promotes efficient electron transfer in the amorphous NiMoB structure, thereby increasing the number of active sites and enhancing site activity; (2) The composite material prepared by the present invention can reduce the HER process barrier, accelerate the HER kinetics, and exhibit excellent HER performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0016] Figure 1 Shown is the XRD pattern of NiMo-based crystalline / amorphous heterostructure composite material; Figure 2 is an EDX-Mapping diagram of a NiMo-based crystalline / amorphous heterostructure composite material provided by some embodiments of the present application; Figure 3 Shown is the SEM image of NiMo-based crystalline / amorphous heterostructure composite material; Figure 4Shown is the TEM image of NiMo-based crystalline / amorphous heterostructure composite material; Figure 5 The linear voltammetric polarization curve of NiMo-based crystalline / amorphous heterostructure composite as electrocatalyst in 1 M KOH is shown; Figure 6 Shown is the Tafel plot of NiMo-based crystalline / amorphous heterostructure composite material as electrocatalyst; Figure 7 Shown are the continuous chronopotentiometry curves of NiMo-based crystalline / amorphous heterostructure composites as electrocatalysts at different current densities. DETAILED DESCRIPTION

[0017] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0018] The surface, interface morphology and structure of the product of the present invention are measured by field emission scanning electron microscopy (SEM) and transmission electron microscopy (TEM); the crystal phase contained in the product is measured by X-ray diffractometer (XRD); the element distribution and composition are measured by energy dispersive X-ray spectrometer imaging (EDX-mapping) equipped with TEM; the electrocatalytic hydrogen evolution reaction performance of the product is measured on Shanghai Chenhua electrochemical workstation.

[0019] Example 1 A NiMo-based crystalline / amorphous heterostructure composite material, the specific preparation method of which is as follows: (1) A pair of nickel wires (0.5 mm in diameter) were immersed in 20 mL of 4 M NaOH solution. The depth of the nickel wires was 1.5 cm and the distance between them was kept at 1.5 cm. A two-electrode system was used and the voltage of the alternating current was set to 8 V. The electrochemical stripping treatment was performed for 100 min. After the product was washed by centrifugation with deionized water, 40 mL of deionized water was added and ultrasonically homogenized to form a dispersion of Ni-containing nanosheets. 20 mL of the dispersion was transferred and 10 mL of 21.9 mg mL -1 The ethanol solution of MoCl5 with a mass concentration of 38.6 mg·mL was stirred for 30 min, and then 4 mL of 38.6 mg·mL was added dropwise. -1 The sodium borohydride aqueous solution was stirred for 30 min, and the product was centrifuged, washed and freeze-dried to obtain a composite material precursor powder; (2) Spread the precursor powder on a porcelain boat and place it in the central heating zone of a tube furnace at 5 °C min ‒1 The heating rate was increased from room temperature to 500 ℃ and maintained for 1 h for high temperature heat treatment, and finally naturally cooled to obtain NiMo-based crystalline / amorphous heterostructure composite materials (i.e., c-Ni / a-NiMoB, where c represents crystalline and a represents amorphous).

[0020] The NiMo-based crystalline / amorphous heterostructure composite material prepared above was subjected to characterization performance tests (XRD, EDX-Mapping, SEM, TEM). The specific results are as follows: Figure 1-Figure 4 As shown: Figure 1 The XRD pattern of NiMo-based crystalline / amorphous heterostructure composite material is shown in Figure 2. By comparing with the standard card, it can be confirmed that the obtained composite material contains the crystalline phase of metallic nickel, and the amorphous species cannot be detected by the XRD instrument.

[0021] Figure 2 This is the EDX-Mapping image of the NiMo-based crystalline / amorphous heterostructure composite material. The analysis reveals the uniform distribution of elements such as Ni, Mo and B in the composite material.

[0022] Figure 3 This is a SEM image of a NiMo-based crystalline / amorphous heterostructure composite material. The material exhibits a two-dimensional structure with a rough surface.

[0023] Figure 4 TEM image of NiMo-based crystalline / amorphous heterostructure composite material. Figure 4 a shows that the flake-like two-dimensional structure can be clearly observed, and its surface is irregularly granular; Figure 4 b reveals the heterogeneous interface between the metal crystalline phase and the amorphous structure. Among them, the 10 times lattice distance (10d) of 2.06 nm in the lattice fringe region corresponds to the (111) plane of crystalline metal Ni; and the structures surrounded by dotted lines are all amorphous regions. The above structural characterizations all indicate that a crystalline / amorphous heterostructure composite material has been prepared.

[0024] Example 2 The NiMo-based crystalline / amorphous heterostructure composite material obtained above was used as a catalyst for hydrogen evolution reaction in water electrolysis for performance testing, and the specific process was as follows: (1) Preparation of electrocatalyst working electrode: Firstly, 5 mg NiMo-based crystalline / amorphous heterostructure composite material powder, 40 μL 5 wt% nafion solution and 960 μL ethanol were weighed and added into a centrifuge tube. Secondly, the centrifuge tube was suspended in an ultrasonic cleaner and ultrasonically treated for more than 60 min to form a relatively uniform ink-like catalyst dispersion in the centrifuge tube. Finally, 8 μL of catalyst ink was dropped onto the surface of a 3 mm diameter glassy carbon electrode disk using a pipette, and the electrochemical performance was tested after it was naturally dried to form a film.

[0025] (2) Electrochemical performance study: The electrochemical performance test was carried out on a Shanghai Chenhua electrochemical workstation (model CHI760E). The electrolyte used was 1 mol·L –1 KOH aqueous solution; the three-electrode system used is: the electrocatalyst-modified glassy carbon electrode as the working electrode, the graphite rod as the auxiliary electrode, and the saturated calomel electrode (SCE) as the reference electrode. According to the Nernst equation, the potential in the test is converted into the reversible hydrogen electrode potential ( E RHE ); Subtract 0 V from E RHE The HER overpotential η .

[0026] The three-electrode configuration was immersed in the electrolyte and then connected to the workstation. The following operations were performed: (i) –1 The linear voltammetric test was performed at a rate of 1000 volts to obtain the polarization curve; (ii) based on the data obtained from the polarization curve (potential E RHE and current density j ),Establish E RHE and log|current density ( j , mA cm –2 )|, the Tafel slope of the electrocatalyst working electrode in the HER process can be calculated; (iii) continuous chronopotentiometry tests at different current densities are performed to obtain the stability test results of the prepared electrocatalyst working electrode, the results of which are shown in FIG. Figure 5-Figure 7 As shown: Figure 5 The linear voltammetric polarization curve of NiMo-based crystalline / amorphous heterostructure composite as electrocatalyst in 1 M KOH. The test results show that the crystalline Ni / amorphous NiMoB heterostructure composite exhibits excellent alkaline HER electrocatalytic activity, which produces 10 mA·cm –2 The benchmark current density (comparable to that produced by a solar device with an efficiency of 12.3%) requires only 55 mV overpotential.

[0027] Figure 6 The Tafel curve of NiMo-based crystalline / amorphous heterostructure composite as electrocatalyst. The figure shows that the Tafel slope of NiMo-based crystalline / amorphous heterostructure composite is only 44.7 mV·dec –1 The extremely low Tafel slope value indicates that the composite material has fast alkaline hydrogen evolution reaction kinetics.

[0028] Figure 7 The continuous time potential curve of NiMo-based crystalline / amorphous heterostructure composite material as electrocatalyst at different current densities. The test shows that the composite material has outstanding durability, and stable potential curves are obtained at different current densities, and 50 mA·cm is obtained after 25 h of testing. -2 There is still no obvious decrease in the potential.

[0029] The embodiments of the present application are described above in conjunction with the accompanying drawings. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the core idea of ​​the present application, but the present application is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the inspiration of the present application, ordinary technicians in this field can also make many forms without departing from the scope of protection of the purpose of the present application and the claims, all of which are within the protection of the present application.

Claims

1. A method for preparing a NiMo-based crystalline / amorphous heterostructure composite material, characterized in that: The following steps are involved: S1: immersing a pair of nickel wires in a NaOH solution, electrochemically exfoliating under an alternating current voltage, centrifugally washing, and ultrasonicating to obtain a dispersion of Ni-containing nanosheets; S2: adding the dispersed liquid of the Ni element nanosheets to the ethanol solution containing MoCl5, stirring, then adding the sodium borohydride solution, stirring for reaction, centrifuging, washing, and drying to obtain a precursor powder of the composite material; S3: placing the precursor powder of the composite material in a tubular furnace and maintaining a flowing hydrogen / argon mixed atmosphere for high temperature annealing to obtain the NiMo-based crystalline / amorphous heterostructure composite material.

2. The preparation method according to claim 1, characterized in that: The NiMo-based crystalline / amorphous heterostructure composite material is formed of a heterostructure of crystalline Ni and amorphous NiMoB; The lattice distance in the NiMo-based crystalline / amorphous heterostructure composite material corresponds to Ni (111).

3. The preparation method according to claim 2, characterized in that: The Ni content of the NiMo-based crystalline / amorphous heterostructure composite material is 10 wt%-20 wt%, and the Mo content is 50 wt%-70 wt%.

4. The preparation method according to claim 1, characterized in that: The volume ratio of the Ni-containing nanosheet dispersion, the MoCl5-containing ethanol solution and the sodium borohydride solution is 10:5:

2.

5. The preparation method according to claim 3, characterized in that: The mass concentration of the Ni-containing nanosheet dispersion is 1 mg·mL -1 ~ 3 mg mL -1 ; The mass concentration of the ethanol solution containing MoCl5 is 20 mg·mL -1 ~25 mg mL -1 ; The mass concentration of sodium borohydride solution is 30 mg·mL -1 ~ 50 mg mL -1 .

6. The preparation method according to claim 1, characterized in that: The voltage of the alternating current is 7 V to 9 V; the time of the electrochemical stripping is 80 min to 120 min.

7. The preparation method according to claim 1, characterized in that: The specific parameters for maintaining the flowing hydrogen / argon mixed atmosphere are: 50 mL·min -1 ~ 70 mL·min -1 A 10% hydrogen / 90% argon mixed atmosphere was introduced at a gas flow rate of .

8. The preparation method according to claim 1, characterized in that: The specific parameters of the high temperature annealing treatment are as follows: At 5 ℃·min -1 The heating rate was increased from room temperature to 400 ℃~600 ℃, then maintained for 0.5 h~2 h, and finally cooled naturally to room temperature.

9. A NiMo-based crystalline / amorphous heterostructure composite material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the NiMo-based crystalline / amorphous heterostructure composite material as claimed in claim 9 as an electrocatalyst, characterized in that: The NiMo-based crystalline / amorphous heterostructure composite material is used as an electrocatalyst for electrolyzing water to generate hydrogen.

Citation Information

Patent Citations

  • Electrode material with crystalline-amorphous concerted catalytic interface and preparation method thereof

    CN113668011A

  • Preparation method and application of Mn-doped CoP / MXene heterostructure composite material

    CN116791140A

  • Crystalline nickel / amorphous molybdenum carbide heterostructure electrocatalyst and preparation method and application thereof

    CN117364147A

  • Preparation method and application of Mo-doped Cu2S / Ni3S2 / NF composite material with heterostructure

    CN118895527A

  • Nickel-based compound-amorphous chromium family heterojunction self-supporting electrode and preparation method and application thereof

    CN119020806A